Measurement of ion transport properties in ion exchange membranes for photoelectrochemical water splitting - Lucas, Éowyn; Han, Lihao; Sullivan, Ian; Atwater, Harry A.; Xiang, Chengxiang (Frontiers in Energy Research, 2022)
Photoelectrochemical (PEC) water-splitting systems have the unique ability to produce renewable hydrogen directly from sunlight, independent of the electrical grid. These systems are therefore appealing technological options for resilient long-term energy storage. Ion selective membranes, such as monopolar and bipolar membranes, are a vital component of PEC water-splitting systems. These membranes allow for ionic conduction between the cathode and anode chambers, separation of products, and improved catalyst environments for reactions. In order to measure key properties and to study the performance of these ion exchange membranes, it is imperative to develop a robust testing protocol that can be used across the field. This paper introduces two standard electrochemical cells designed to directly measure ion transport properties in monopolar and bipolar membranes. The first electrochemical cell uses commercially available Pt disk electrodes to preform electrochemical impedance spectroscopy (EIS) and reliably measure through-plane conductivity of monopolar membranes. The second electrochemical cell uses four-point measurements with Luggin capillaries and a series of membrane configurations to perform current density-voltage and Faradaic efficiency (FE) measurements for water dissociation (WD) reactions on bipolar membranes. The cell designs and techniques laid out below allow for accurate measurement of ion transport parameters in ion exchange membranes, direct comparison of membranes being developed across the field, and in turn, greater advancements in ion exchange membranes and PEC water-splitting systems.